Plasma Levels of Neudesin and Glucose Metabolism in Obese and Overweight Children - Vergani, Edoardo; Bruno, Carmine; Cipolla, Clelia; Currò, Diego; Mancini, Antonio (Frontiers in Endocrinology, 2022)
Childhood overweight and obesity are among the major health problems of modern times, especially in Western countries, due to their association with increased cardiovascular and cancer risk in adulthood. Neudesin, a recently discovered peptide secreted mainly in the brain and adipose tissue, is being investigated for its possible activity as a negative regulator of energy expenditure. We conducted a cross-sectional observational study with the aim of testing the hypothesis that plasma levels of neudesin can be modified in obese and overweight children and to evaluate any possible relationship between plasma neudesin levels and metabolic and anthropometric parameters. 34 Children (Tanner’s stage 1) were included and divided in two groups according to Cole's criteria. Group A included obese and overweight children (23 patients, 17 females and 6 males, aged 4-10 years); Group B included healthy normal-weight children (11 subjects, 7 females and 4 males, aged 3-10 years). Metabolic (glucose and insulin, total, LDL- and HDL-cholesterol, triglycerides, uric acid) and hormonal (fT3, fT4, TSH, IGF-1, leptin) parameters were evaluated. HOMA-IR and QUICKI index and the area under the curve (AUC) of glucose and insulin after oral glucose load were calculated in obese and overweight children. Neudesin was measured by ELISA. Neudesin levels were significantly higher in obese/overweight children than in controls. In obese and overweight children, plasma neudesin levels were significantly directly correlated with blood glucose and glucose AUC. Taken together, these results, although preliminary, may suggest a possible age-related role of neudesin in glucose homeostasis in obese/overweight children.